Proverbes dramatiques w polskiej dramaturgii XIX wieku - Szumska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article presents the nineteenth-century history of the genre called proverbe dramatique – a transformation from a theatrical form the origins of which lie in the seventeenth-century dinner games to a work of literature. The sketch presents the origins and the development of the genre, its thematic and formal evolution; characteristic features, including in particular syncretism of genres – combining proverbs with, among others, comedy of manners and romantic comedy, comedy of errors and characters, tragicomedy, farce and sketch – characteristic of this period; the place of dramatic proverbs in the works of selected writers, including, in particular, Jan Chęciński and Aleksander Fredro; and the presence of stage proverbs in Polish drama and in the repertoires of the nineteenth-century theatres.